Active tectonics and paleo-earthquakes in north Yumu Shan, northern Tibetan Plateau: Insights from structural analysis and radiocarbon dating - Wang, Ye; Chen, Xuanhua; He, Chengguang; Xiao, Yongjun; Shao, Zhaogang; Han, Jian’en; Li, Bing; Zhang, Yiping; Ding, Weicui; Xu, Shenglin; Han, Lele (Frontiers in Earth Science, 2023)
The Yumu Shan is located at northern margin of the Tibetan Plateau and southern margin of the Hexi corridor, NW China. It is characterized by the development of several NE-protruding arcuate topographic belts in its north slope. The arcuate belts consist of several linear distributed scarps along the Wutongquan spring, the ancient Camel City, and the Xiaogengzi area, south to the Gaotai City. Our detailed field mapping and structural analysis reveal NE-directed active anticline folding and related lacustrine sediments along the arcuate belts. Radiocarbon dating of plant charcoal samples in the lacustrine sedimentary layers yields a 14C age of AD 178±42, which is close to the time of the 180AD/Ms7.5 earthquake at the Biaoshi City (ancient Zhangye City), during the Eastern Han Dynasty. We suggest that the formation of the arcuate belts is resulting from the active blind thrust faulting and related folding in northern margin of the Tibetan Plateau, due to a series of historical earthquake activities. The paleo-earthquakes, especially the 180AD/Ms7.5 Biaoshi earthquake, might have led to the formation of topographic scarps and related deposition of lacustrine sediments. This will be responsible for the uplift and northeastward growth of the Tibetan Plateau. We determine the XiaoGengzi Fault, the northernmost blind thrust in this area, as the North-Boundary Thrust (NBT) which defines the northeastern margin of the Tibetan Plateau.